2022
DOI: 10.3390/ijms232214469
|View full text |Cite
|
Sign up to set email alerts
|

Cardio-Vascular Interaction Evaluated by Speckle-Tracking Echocardiography and Cardio-Ankle Vascular Index in Hypertensive Patients

Abstract: Hypertension increases arterial stiffness, leading to dysfunction and structural changes in the left atrium (LA) and left ventricle (LV). However, the effects of hypertension on the right atrium (RA) and the right ventricle are still not fully understood. The purpose of this study was to clarify whether there is an interaction not only in the left ventricular system but also in the right ventricular system in hypertensive patients with preserved LV ejection fraction. The current retrospective observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Cardiovascular interaction has recently been demonstrated using CAVI, not only in the left heart system but also in the right heart system. 9,10 Recently, much evidence has been reported on SGLT2 inhibitors and ARNI for heart failure. [11][12][13] However, there has not yet been a report using CAVI that focuses on effects of the "Fantastic Four" on the cardiovascular interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular interaction has recently been demonstrated using CAVI, not only in the left heart system but also in the right heart system. 9,10 Recently, much evidence has been reported on SGLT2 inhibitors and ARNI for heart failure. [11][12][13] However, there has not yet been a report using CAVI that focuses on effects of the "Fantastic Four" on the cardiovascular interaction.…”
Section: Discussionmentioning
confidence: 99%
“…First, hypertension is an established risk factor for abnormal GLS regarded as an early and sensitive marker of subclinical LV systolic dysfunction. 25 In addition, it has been reported that increased CAVI is associated with worse cardiac structure and function in hypertensive patients, 26,27 suggesting that hypertension appeared to mediate the associations of CAVI with worse cardiac structure and function. Further investigations of the hypertension-specific pathophysiological mechanisms are warranted.…”
Section: Ta B L Ementioning
confidence: 99%
“…Most recently, there is a growing body of evidence about the clinical utility of the speckle tracking of the RV [109]. It undergoes remodeling in many cardiac conditions, among them HHD [24].…”
Section: Speckle Tracking Of Ventriclesmentioning
confidence: 99%